Design, synthesis, in silico studies, and antiproliferative evaluations of novel indolin-2-one derivatives containing 3-hydroxy-4-pyridinone fragment. (15th August 2022) - Shirvani, Pouria; Fayyazi, Neda; Van Belle, Siska; Debyser, Zeger; Christ, Frauke; Saghaie, Lotfollah; Fassihi, Afshin
Graphical abstract: Highlights: A series of indolin-2-one derivatives with the 3-hydroxy-4-pyridinone moiety were designed and synthesized. The in vitro cytotoxicity of the compounds was evaluated. Compound 10 k demonstrated promising antiproliferative activity (EC50 = 0.69 μM) against MOLM-13. The most active compounds were docked within the active site of FLT3 enzyme. Abstract: Keeping in view the pharmacological properties of indolinones as promising scaffold as kinase inhibitors, herein, a novel series of 3-hydrazonoindolin-2-one derivatives bearing 3-hydroxy-4-pyridinone moiety were synthesized, studied by molecular docking, and fully characterized by spectroscopic techniques. All the prepared compounds were evaluated for their cytotoxicity attributes against a panel of tumor cell lines, including non-small cell lung cancer (A549), breast carcinoma (MCF-7), acute myeloid leukemia (AML), and chronic myeloid leukemia (CML). They displayed moderate to promising antiproliferative effects toward A549 and MCF-7 cells but remarkable results against AML and CML. Especially, compound 10k was found to be more potent against AML (EC50 = 0.69 μM) compare to the other halogen-substituted derivatives. FMS-like tyrosine kinase 3 (FLT3) is known to be expressed in AML cancer cells. The molecular docking studies demonstrated that our prepared compounds were potentially bound to AML active site through essential H-bond and other vital interactions with critical binding residues.